2020
DOI: 10.1038/s41419-020-2621-y
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-130b-3p targets SIK1 to inhibit medulloblastoma tumorigenesis

Abstract: Exosomes are an important carrier for cell communication. miRNAs in exosomes are potential biomarkers and therapeutic targets in different types of cancer. However, the role of exosomal miRNAs in medulloblastoma (MB) patients is largely unknown. In this study, we reported that there was a higher level of miR-130b-3p in exosomes derived from MB patient plasma compared with exosomes from healthy control plasma. Exosomes from MB patient plasma could transfer miR-130b-3p to an MB cell line and played suppressor ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 44 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…Among these, we focused on SIK1. Previous studies have shown that SIK1 is a tumor suppressor and is regulated by transcription factors in some cancers [ 26 29 , 49 ]. We therefore speculated that BMI1 might be involved in regulation of SIK1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, we focused on SIK1. Previous studies have shown that SIK1 is a tumor suppressor and is regulated by transcription factors in some cancers [ 26 29 , 49 ]. We therefore speculated that BMI1 might be involved in regulation of SIK1 expression.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Another study found that exosomal miR-130b-3p targeted serine/threonine-protein kinase 1 through the p53 signal pathway could inhibit medulloblastoma tumorigenesis. 24 As for miR-3614-3p, a study has reported that the overexpression of it can down-regulate the expression of TRIM25 to inhibit the growth of breast cancer cells. 25 MiR-365a-3p was proved to inhibit the expansion and metastasis of colorectal cancer cells partly via inhibiting the expression of ADAM10 and JAK/STAT signal.…”
Section: Discussionmentioning
confidence: 99%
“…As a new intracellular communication toll, exosomes play a vital role in tumor progression (Huang et al, 2020; Zhang et al, 2020). Exosomes are considered to be an ideal drug delivery vehicle, which mediate cell‐to‐cell communication by delivering DNAs, RNAs, and proteins.…”
Section: Discussionmentioning
confidence: 99%